LEGO DC comics super heroes. The Flash [videorecording (Blu-Ray)] - Krieg, Jim; Adams, Jeremy (Screenwriter) (Warner Bros. Home Entertainment, 2018)
The morning sun shines on the jewel of the Metropolis skyline, The Daily Planet building. But when the Joker decides this building needs a renovation, it's time to sound the trouble alert because all bricks are about to break loose.